AKULTURASI BUDAYA DALAM KESENIAN SETREK DI DUSUN KEDUNGAN III, SAMBENG, BOROBUDUR, MAGELANG - Langen Bronto Sutrisno (Institut Seni Indonesia Surakarta, 2011)
Setrek at Kedungan III is a type of traditional art terbangan or slawatan that serves as a medium for preaching Islam. As a kind of traditional art slawatan, seems to blend aesthetic elements having Islamic art with aesthetic elements of traditional folk art is a form of acculturation that reflect local creativity. The influence of Islamic art is not meant to change the overall form of the choreography, but the elements of Islam is more of a formality breath Islamic values in the face of traditional arts for the purpose of preaching the religion of Islam. Therefore, it remains in the form of presentation format with a touch of tradition Islamic breath. For example, the presentation of dance movement found hardly breathing motion Islam except Takbiratul Ihram Allohu Akbar, which is the figure Kyai Ba’in representation a scholar with typical Islamic fashion, Islamic airway motorcade given poetry book Al Barjanzi comes flying instruments and music representing jidor Islam. Breath of Islam is actually more of a legal spirit of Islam in the arts setrek the hope of all the players and spectators can practice Islam in their daily lives. Therefore, the media propaganda can be seen in any expression of Islamic values in relation to the God The Almighty and His Prophet Muhammad SAW. Thus every movement and musical accompaniment or poem in the arts setrek have imbued the values of Islam. Icons is thus important to understand that they can safely live in this world and in the hereafter. The presence of Islam in the breath of artistic development setrek looks enrich appearance, so the presence of this art in people’s lives Kedungan III boost the quality of the religion of Islam, although they were aware the remnants of ancient beliefs still characterize setrek arts, such as ndas-ndasan attraction in the form of imitating animal attraction . Variations attraction ndas-ndasan procession around the village with aim to expel the influence of evil spirits.Key words : setrek, acculturation, traditional.